Constantes de Movimento para o Modelo Sinh-Gordon Supersimétrico N = 1 com Defeito - Spano, Nathaly Infantini [UNESP] (2014)
From the generators of the Kac-Moody superálgebra 's TIL'l(2,1) write the Lax pair for the supersymmetric sinh-Gordon model. In addition, we ?nd that through the zero curvature obtained the Lax equation reproduces the equations of motion of the model. For the analysis of defective theories calculated by means of a gauge transformation, the default matrix for the model sinh supersymetric Gordon, and present the result similar to the sine-Gordon model. We also note that in the defect region, the ?eld equations of the theory obey the type of Backlund transformations. The energy and momentum for the super sinh-Gordon model were also obtained from a general expression that allows us to obtain the in?nite set of conserved charges for style. In addition, the contributions of the defect these quantities have also been found